2016
DOI: 10.1002/wsb.665
|View full text |Cite
|
Sign up to set email alerts
|

Is it a mottled duck? The key is in the feathers

Abstract: The Florida mottled duck (Anas fulvigula fulvigula) is threatened by introgression through hybridization with feral mallards (A. platyrhynchos). An essential component in managing this threat is the ability to accurately distinguish mottled ducks from mallards and hybrids in the wild. We provide a genetically cross‐validated phenotype key that accurately identifies mottled ducks. We collected data on structural and plumage traits from museum specimens of Florida, USA, mottled ducks and mallards to identify mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Furthermore, only ~60% of phenotypically identified hybrids were true hybrids with ~12% and ~25% of remaining samples being actually “pure” mallards or black ducks, respectively (Figure , Table ; Supporting Information Table ). Our “error rates” are similar to those reported between mallards and Florida Mottled ducks before a genetically vetted field key was developed (Bielefeld et al, ). With the exception of western mallards, all Mississippi and Atlantic flyway mallards, black ducks, and hybrids were sampled from the 2010 U.S.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, only ~60% of phenotypically identified hybrids were true hybrids with ~12% and ~25% of remaining samples being actually “pure” mallards or black ducks, respectively (Figure , Table ; Supporting Information Table ). Our “error rates” are similar to those reported between mallards and Florida Mottled ducks before a genetically vetted field key was developed (Bielefeld et al, ). With the exception of western mallards, all Mississippi and Atlantic flyway mallards, black ducks, and hybrids were sampled from the 2010 U.S.…”
Section: Discussionsupporting
confidence: 83%
“…For example, the presence of an anterior and/or posterior white‐wing bar across the speculum is currently a primary character used to identify hybrids between mallards and black ducks. However, a recent study found the same character thought to be indicative of hybrids between mallards and mottled ducks in 10% of genetically “pure” mottled ducks (Bielefeld et al, ). Thus, for scenarios of recent divergence in which ancestral characters may be maintained across lineages, it is critical to genetically vet phenotypic characters to confirm their diagnosability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Stocks of mottled ducks used in these translocations were composed of 2 subspecies that are distinct in genetics, phenotype, and ecology (Bielefeld et al 2010(Bielefeld et al , 2016Baldassarre 2014;Peters et al 2016). In short, Western Gulf Coast mottled ducks (A. f. maculatlus) are indigenous to coastal marshes surrounding the Gulf of Mexico from Mexico and north and east through Texas, Louisiana, Mississippi, and Alabama, USA.…”
mentioning
confidence: 99%
“…Due to phenotypic variation among sex and age classes in other waterfowl, the use of such characters alone has led to an overestimation of hybridization in some species (Williams et al 2005; e.g. mottled duck × mallard hybridization, Bielefeld et al 2016; Mexican duck × mallard hybridization, Hubbard 1977, Scott and Reynolds 1984). Therefore, while field observations suggest hybridization between goldeneye is rare, overall rates of hybridization and inter‐specific gene flow are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%